Synthesis of inorganic doped polyvinyl alcohol/hydroxypropyl methyl cellulose mixed matrix membrane for pervaporative separation of dimethyl carbonate/methanol mixtures - Ünlü, Derya (Korean Institute Chemical Engineers, 2020)
Inorganic loaded Polyvinyl Alcohol/Hydroxypropyl Methyl Cellulose (PVA/HPMC) mixed matrix composite membranes were synthesized by filling phosphomolybdic acid (PMA) into PVA/HPMC matrix. The obtained results indicate that the swelling degree of the PMA loaded PVA/HPMC blend membranes enhances with excess PMA amount or high feed methanol (MeOH) concentration. The effects of HPMC ratio in blend membranes, PMA content, feed methanol concentration and operation temperature on separation success of pervaporation (PV) were also examined. The consequences demonstrate that the separation factor decreased with PMA amount and led to the ultimate value at 4 wt% PMA amount. Then the increase of PMA content resulted in the decline of the separation factor. Under all conditions, PMA doped mixed matrix composite membrane had a higher separation factor and flux values according to the pristine PVA membrane. Of all the membranes studied, while the flux increased by the high temperature or feed methanol concentration, the separation factor of MeOH decreased. While the operation temperature was 50 degrees C, the feed methanol concentration was 10 wt%; 4 wt% PMA doped mixed matrix composite membrane has significant separation performance with a flux of 1.31 kg/m(2)h and separation factor of 121.04.
Keywords: Dimethyl Carbonate; Methanol; Pervaporation; Phosphomolybdic Acid